Mask of the deer woman - Dove, Laurie L. (Berkley, 2025)
"To find a missing young woman, the new tribal marshal must also find herself. At rock bottom following her daughter's murder, ex-Chicago detective Carrie Starr has nowhere to go but back to her roots. Starr's father never talked much about the reservation that raised him, but they need a new tribal marshal as much as Starr needs a place to call home. In the last decade, too many young women have disappeared from the rez. Some dead, others just... gone. Now, local college student Chenoa Cloud is missing, and Starr falls into an investigation that leaves her drowning in memories of her daughter-the girl she failed to save. Starr feels lost in this place she thought would welcome her. And when she catches a glimpse of a figure from her father's stories, with the body of a woman and the antlers of a deer, Starr can't shake the feeling that the fearsome spirit is watching her, following her. What she doesn't know is whether Deer Woman is here to guide her or to seek vengeance for the lost daughters that Starr can never bring home"--